Edukacja międzykulturowa w edukacji wczesnoszkolnej: perspektywa historyczno-pedagogiczna i dobre praktyki nauczycieli na przykładzie Prywatnej Szkoły Podstawowej „Mieszko” w Poznaniu - Adamczewski, Jakub; Płonka, Joanna (Biuletyn Historii Wychowania, 2020)
The aim of this article is to present a historical perspective on intercultural education, contemporary methods of supporting foreign students as well as the role of the teacher and the specific competence required to teach effectively in an intercultural environment. Contemporary methods of support are presented based on the example of good educational practice taking place at “Mieszko” Private Elementary School in Poznań. Actions that can be initiated by a teacher in early education have been divided into four areas: physical, didactic, social and in the classroom. The physical area addresses the issue of school space and activities that help to identify and address students’ difficulties in areas related to senses and coordination. The didactic area represents cultural events designed to entertain and educate; there are also examples of how to equalize educational opportunities among students. The subsequent area, encompassing activities carried out within a class group, show intercultural activities included in the curriculum and indicate which activities may help to control difficult behaviours of children. The social area activities are designed to support students in maintaining meaningful relationships with their peers and collaborating with other organizations that can complement and enrich intercultural formal education.